Cost effectiveness of home based population screening for Chlamydia trachomatis in the UK: economic evaluation of chlamydia screening studies (ClaSS) project. Issue 7614 (26th July 2007) - Roberts, Tracy E; Robinson, Suzanne; Barton, Pelham M; Bryan, Stirling; McCarthy, Anne; Macleod, John; Egger, Matthias; Low, Nicola
Abstract : Objective To investigate the cost effectiveness of screening for Chlamydia trachomatis compared with a policy of no organised screening in the United Kingdom. Design Economic evaluation using a transmission dynamic mathematical model. Setting Central and southwest England. Participants Hypothetical population of 50 000 men and women, in which all those aged 16-24 years were invited to be screened each year. Main outcome measures Cost effectiveness based on major outcomes averted, defined as pelvic inflammatory disease, ectopic pregnancy, infertility, or neonatal complications. Results The incremental cost per major outcome averted for a programme of screening women only (assuming eight years of screening) was £22 300 (€33 000; 45 000) compared with no organised screening. For a programme screening both men and women, the incremental cost effectiveness ratio was approximately £28 900. Pelvic inflammatory disease leading to hospital admission was the most frequently averted major outcome. The model was highly sensitive to the incidence of major outcomes and to uptake of screening. When both were increased the cost effectiveness ratio fell to £6200 per major outcome averted for screening women only. Conclusions Proactive register based screening for chlamydia is not cost effective if the uptake of screening and incidence of complications are based on contemporary empirical studies, which show lower rates than commonly assumed. These data are relevant to discussions about the cost effectiveness of the opportunistic model of chlamydia screening being introduced in England.